The impact of cost of production and price fluctuation on the revenues of pepper farmers - Aley Looi, Rhemaneeta Allan; Daud, Adrian; Teruki, Neilson; Alwie, Aryaty (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
This paper seeks to explain the socio-economic impact of the pepper farmers based on the cost of production and global price fluctuation. The impacts on the farmers will be examined to gain insights on their income from pepper farming. Efficiency in farm management is measured and compared to the standard that has been set by the Malaysian Pepper Board (MPB). Benefit-cost ratio, gross margin and net income will be calculated to estimate the cost and revenue. Time series model is used in calculating price fluctuation and forecasting of price. Production costs is dependent on few factors and the efficiency in managing these will have an impact on farmers’ income. There should be a threshold price for which pepper can be an attractive crop for farmers.